2015
DOI: 10.1002/pro.2668
|View full text |Cite
|
Sign up to set email alerts
|

On the lack of polymorphism in Aβ‐peptide aggregates derived from patient brains

Abstract: The amyloid beta (Ab) oligomers and fibrils that are found in neural tissues of patients suffering from Alzheimer's disease may either cause or contribute to the pathology of the disease. In vitro, these Ab-aggregates are characterized by structural polymorphism. However, recent solid state NMR data of fibrils acquired post mortem from the brains of two Alzheimer's patients indicate presence of only a single, patient-specific structure. Using enhanced molecular dynamic simulations we investigate the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…The terminal Aβ chains in AL 3x6 and AL 3x12 lacking a second β-sheet binding partner were more mobile than the other chains, which is known from other simulation studies [38, 47, 5759]. Overall, our findings for the full-length Aβ40 systems with respect to their structural stability are in agreement with earlier studies [35, 36]. …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The terminal Aβ chains in AL 3x6 and AL 3x12 lacking a second β-sheet binding partner were more mobile than the other chains, which is known from other simulation studies [38, 47, 5759]. Overall, our findings for the full-length Aβ40 systems with respect to their structural stability are in agreement with earlier studies [35, 36]. …”
Section: Resultssupporting
confidence: 92%
“…The individual Aβ filaments formed a linear arrangement, showed a strong twisting of the stacks relative to each other, or underwent dissociation of one stack. Three Aβ layers are thus not sufficient to stabilize a triple-fibril conformation in accordance with previous findings [35, 36]. Thus, these systems were excluded from further analysis.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Even though it would contribute to the binding, to make it stronger, this small region, being highly flexible, is expected to have a small favorable free energy contribution. We chose not to use the 2M4J structure of 1–40 Aβ fibril determined from a single patient 69 , since more research into the variability between structures found in patients is needed before using one or the other structure as the most probable structure formed in vivo 69 and, this structure in particular was found to be unstable, by computer simulation 70 . We chose the 2LMQ structure for the fibrils formed in vitro to be the one to characterize the fibrils that we used experimentally to interact with Tat, as they were prepared in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…Solid-state NMR experiments distinguished at least three Aβ polymorphic amyloid structures, which were recently analyzed in silico. 54 The two-fold symmetry fibril structure considered here was obtained in vitro under agitated conditions, 4 whereas under in vitro quiescent conditions three-fold symmetry fibrils form. 5 In both structures, Aβ peptides adopt strand-turn-strand folds, in which the NT binding sites (Tyr10, Val12, His14) exist in simular conformations.…”
Section: Fddnp Biomarker Binds To Aβ Fibril At Two Distinct Locationsmentioning
confidence: 99%